Food Safety Situations in Thailand with Regard to their Thai’s Food Safety Knowledge and Behaviors - Masami T. Takeuchi,; Kangsadan Boonprab, (Agriculture and Natural Resources, 2006)
Interviews with representatives of organizations working on food safety in Thailand (n=15) revealed that all interviewees were confident that food safety situation in Thailand has remarkably improved in the last 5 years (2000-2005). However, minimal regulatory attention to domestic food safety compared to the enormous focus on exported food was a common concern. Whether food biotechnology should be used in Thailand was an intense topic within their organizations. Surveys of Thai consumers (n=251) revealed that most (77%) were generally concerned about safety of food, but their information sources were limited. More than 40% thought the government “seldom” or “never” provided adequate food safety information. The consumers mentioned that chemical contamination (78%), food vendor personal hygiene (46%), bacterial/viral contamination (33%), bird flu (10%) and GMO foods (3%) were problems. Prevention of foodborne illnesses, safety of GMO foods and chemical contamination of food were very or somewhat important to 92, 61 and 96% of participants, respectively. Among Thai, Japanese and American consumers, Thai consumers were less likely to follow recommended food handling behaviors. Concerning use of biotechnology in food, Thai consumers most frequently choose a neutral response; Japanese chose negative responses and Americans chose positive responses.